SISTEM PAKAR DIAGNOSA PENYAKIT SKIZOFRENIA MENGGUNAKAN METODE DEMPSTER SHAFER - Andhi rizki gunawan (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
Schizophrenia is a mental disorder in the thought process that is disharmonious (cracked or broken) between picker, emotional, desire, psychomotor processes accompanied by distortion of reality caused by delusions (delusions), hallucinations, associations divided until incoherence appears, both men and women can suffer from schizophrenia. The most vulnerable age to this disease is around the age of 15 years to 35 years. The design of this expert system was made with the aim of creating a temporary information and consultation system forum through the application made, which is based on symptom data obtained from the field of health (psychology) and is expected to make it easier for the public to diagnose schizophrenia symptoms early. To diagnose schizophrenia with an expert system, a method is needed to diagnose it, therefore in this study apply the Dempster-Shafer method. The Dempster-Shafer theory is the representation, combination and propogation of uncertainty, where this theory has several characteristics that are instructively in accordance with the way an expert thinks, but a strong mathematical basis. The results of the system testing that has been created can provide information as well as a way to temporarily diagnose schizophrenia.The web-based expert system that has been created using the Dempster Shafer method can diagnose schizophrenia temporarily.